2021
DOI: 10.3390/electronics11010075
|View full text |Cite
|
Sign up to set email alerts
|

Robust Hybrid Beam-Forming for Non-Orthogonal Multiple Access in Massive MIMO Downlink

Abstract: This paper presents hybrid precoding for a non-orthogonal multiple access (NOMA) transmission scheme in a millimeter wave (mmWave) massive MIMO (mMIMO) downlink. In hybrid precoding, the analog precoder is obtained by the orthogonalization of the users’ channel vectors to minimize inter-beam interference. The digital precoder consists of a zero-forcing precoder to minimize inter-user interference. In order to break the barrier of one user per beam, we utilize the NOMA within the beam for power domain multiplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the last several years, many elements of millimeter waves have been reported in Rangan et al 3 and Huang et al 17 The promise and challenges of mmWave technology were discussed by Wu et al 18 The future of the 5G network using mmWave technology was discussed by Chakraborty et al 19 The mMIMO systems are difficult to implement due to space constraints. However, the mmWave frequency range makes it conceivable because the antenna size is dramatically decreased at such high frequencies proposed by Alraddady et al 20 The hybrid beamforming technique reduces cost and power consumption using a small number of RF chains proposed by Chataut et al 12 It also advocated an all‐inclusive opinion of HB for 5G and beyond mmWave systems, depending on a new taxonomy for different hardware mechanisms, but this paper needs to consider the effects of using a small number of RF chains. Lin et al 21 suggested and analyzed the quantization of phase shifters for hybrid precoding systems.…”
Section: Related Workmentioning
confidence: 99%
“…In the last several years, many elements of millimeter waves have been reported in Rangan et al 3 and Huang et al 17 The promise and challenges of mmWave technology were discussed by Wu et al 18 The future of the 5G network using mmWave technology was discussed by Chakraborty et al 19 The mMIMO systems are difficult to implement due to space constraints. However, the mmWave frequency range makes it conceivable because the antenna size is dramatically decreased at such high frequencies proposed by Alraddady et al 20 The hybrid beamforming technique reduces cost and power consumption using a small number of RF chains proposed by Chataut et al 12 It also advocated an all‐inclusive opinion of HB for 5G and beyond mmWave systems, depending on a new taxonomy for different hardware mechanisms, but this paper needs to consider the effects of using a small number of RF chains. Lin et al 21 suggested and analyzed the quantization of phase shifters for hybrid precoding systems.…”
Section: Related Workmentioning
confidence: 99%
“…In [9], a cooperative relay NOMA with a massive MIMO system based on the geometricbased stochastic channel model is proposed. In [10], hybrid precoding of millimeter wave large-scale MIMO based on NOMA is presented, which utilizes NOMA with beamforming to reduce the orthogonality error. Reference [11] incorporates code reuse in the proposed signal transmission scheme to access the BER of a MIMO-NOMA system.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in (6,7) considered multiuser performance analysis but did not consider multicell environment as we do in this research. The authors in (8) considered hybrid precoding for non-orthogonal multiple access transmission scheme and achieved better spectral efficiency compared to state of art algorithms but did not consider Kalman algorithm for performance comparison. The authors in (9) considered multicell multiuser environment and analyzed energy efficiency of hybrid precoding but did not consider Kalman based algorithm for performance comparison as we do in this research.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, on single cell single user/multiuser environments, several research works on hybrid precoders/combiners have been done (1,(5)(6)(7)(8) . Some works have also been done on multicell multiuser scenario (9)(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation